Construction and functional analysis of ceRNA regulatory network related to the development of secondary hair follicles in Inner Mongolia cashmere goats - Shang, Fangzheng; Ma, Rong; Rong, Youjun; Pan, Jianfeng; Wang, Min; Niu, Shuran; Qi, Yunpeng; Li, Yanbo; Wang, Zhiying; Lv, Qi; Wang, Ruijun; Su, Rui; et al. (Frontiers in Veterinary Science, 2022)
Cashmere goat hair follicles are divided into primary hair follicles and secondary hair follicles. The primary hair follicles produce coarse hair, and the secondary hair follicles produce cashmere. The development of hair follicles are affected by a variety of signaling molecules and pathways. Studies have shown that non-coding RNAs are widely involved in the development of hair follicles of the goat, including small RNAs (miRNAs), long non-coding RNAs (lncRNA) andcircular RNAs (circRNAs). In recent years, circRNAs, as a new type of circular closed non-coding RNAs, have attracted great attention due to their high stability. However, its regulatory effect on cashmere goat hair follicles mainly focuses on the periodic regulation of secondary hair follicles, and there is no report on the development of cashmere goat hair follicles during fetal period. Therefore, this study was based on the circRNA, miRNA and mRNA expression profiles obtained by whole-transcriptional sequencing of the skin tissue of Inner Mongolia cashmere goat in fetal period (45d, 55d, 65d and 75d), and screened out the morphological changes of hair follicles in different periods. 113 circRNAs related to the development of secondary hair follicles.According to the principle of ceRNA regulatory network, a ceRNA regulatory network composed of 13 circRNAs, 21 miRNAs and 110 mRNAs related to the development of secondary hair follicles was constructed.Then,qRT-PCR and Sanger sequencing identified circRNA2034, circRNA5712, circRNA888 and circRNA9127 were circRNAs.Next,the dual-luciferase reporter gene verified the targeting relationship of circRNA5712-miR-27b-3p-Dll4.In conclusion, this study constructed a ceRNA regulatory network for the development of cashmere goat secondary hair follicles, laying a foundation for the analysis of circRNAs regulating the occurrence and development of cashmere goat secondary hair follicles through the ceRNA mechanism.